Sexual dimorphism based on body proportions and ontogenetic changes in the Brazilian electric ray Narcine brasiliensis (von Olfers, 1831) (Chondrichthyes: Narcinidae) - Rolim, F. A. [UNESP]; Caltabellotta, F. P.; Rotundo, M. M.; Vaske-Júnior, T. [UNESP] (My University, 2015)
Sexual dimorphism in the Brazilian electric ray Narcine brasiliensis from the south‑western Atlantic coast was evaluated based on body proportions and ontogenetic changes. All regions of the body were found to have differences in body proportions between the sexes, except the spiracles. The nature of allometric and isometric relationships differed mainly in terms of the six largest body dimensions. Some of these differences can be supported by the species’ life history. Principal components analysis (PCA) and analysis of similarities (ANOSIM) distinguished the adults’ body proportions by sex. Similarity percentage analysis (SIMPER) selected six variables that best discriminated between the sexes with a cumulative difference up to 70% (tail width, disc width, length between snout and first dorsal fin, pelvic fin width, length between snout and the widest part of the disc, and disc length). It was possible to select seven stable dimensions, both ontogenetic and sexual, that are recommended for use in taxonomic studies. These dimensions were interspiracular distance, spiracle length and width, upper and lower tooth band width, pelvic fin length, and length of posterior lobe of the pelvic fin. It is important to consider the differences in body proportions within a species in order to properly characterise the population and estimate its most reliable parameters.
Keywords: Elasmobranchii; morphometry; relative growth; Torpediniformes